Bioassay-guided isolation of proanthocyanidins with antioxidant activity from peanut (Arachis hypogaea) skin by combination of chromatography techniques. (1st February 2016) - Oldoni, Tatiane L.C.; Melo, Priscilla S.; Massarioli, Adna P.; Moreno, Ivani A.M.; Bezerra, Rosângela M.N.; Rosalen, Pedro L.; da Silva, Gil V.J.; Nascimento, Andréa M.; Alencar, Severino M.
Highlights: The bioassay guided used is effective to isolate antioxidants from peanut skin. Two proanthocyanidins (A1 and A2) were isolated. Proanthocyanidins A1 and A2 do not have synergistic effect. The stereochemistry of the OH group at the 3′ position in A1 is the responsible by its higher bioactivity. Peanut skin is a low cost source of natural antioxidants for food industry. Abstract: Purification and bioassay-guided fractionation were employed to isolate proanthocyanidins with antioxidant activity from peanut skin ( Arachis hypogaea Runner 886). The crude extract was prepared with acetone (60% v/v) and purified using chromatographic methods, including a semipreparative HPLC technique. As a result, two proanthocyanidins were isolated and identified using NMR, epicatechin-(2 β → O → 7, 4 β → 8)-catechin (proanthocyanidin A1) and epicatechin-(β → 2 O → 7, 4 β → 8)-epicatechin (proanthocyanidin A2). Despite the structural similarity, differences were observed in their antioxidant activity. Proanthocyanidin A1 proved to be more active, with EC50 value for DPPH radical scavenging of 18.25 μg/mL and reduction of Fe 3+ –TPTZ complex of 7.59 mmol/g, higher than that of synthetic antioxidant BHT. This compound evaluated by ABTS + was similar to that of natural quercetin. Therefore, peanut skin is an important source of bioactive compounds that may be used as a mild antioxidant for food preservation.